Port Cities as Areas of Transition Ethnographic Perspectives - Kokot, Waltraud; Gandelsman-Trier, Mijal; Wildner, Kathrin; Wonneberger, Astrid (Urban Studies, 2008)
In the past decades, international port cities have been strongly affected by global transformation processes, dramatically altering life and work around the ports, the built environment and public imagery of urban waterfronts. Based on recent theories of city-port development, the ethnographic studies in this volume focus on local stakeholders' perceptions and strategies in port cities in Europe and Latin America. This book covers a wide variety of urban fields, from traditional dockland communities, inland waterway sailors and new forms of migration and exile, to active agents of urban transformation.